Comparing anthropometric and performance test results across playing levels and evaluating their correlation with game performance in women's collegiate basketball - Uysal, A. A.; Stone, M. H.; Carroll, K.; Faust, T. (The Journal of Strength and Conditioning Research, 2025)
This research was an investigation of the relationship between body composition, athletic performance test results, and basketball game performance in women's NCAA Division 1 guards. The study also compared anthropometric and athletic performance test results between women's NCAA Division 1 and women's NAIA guards. Forty female subjects were selected retrospectively, including 21 NCAA Division 1 and 19 NAIA basketball guards. Countermovement jump (CMJ) and isometric mid-thigh pull (IMTP) force-time metrics were analyzed as athletic performance test results. Body mass index, body mass, body fat ratio, fat-free mass (FFM), and height were analyzed as anthropometric parameters. Basketball game performance metrics included minutes per game, points per game, rebounds per game, and playing efficiency (EFF). Pearson correlation analyses and independent samples t tests were used for statistical analysis. No statistically significant relationship was found between any of the athletic performance test results and game performance (p > 0.05). Statistically significant correlations were found between FFM and EFF (p = 0.030, r = 0.475), and FFM with rebounds per minute (p = 0.042, r = 0.447). NCAA Division 1 guards had significantly higher FFM (p = 0.006) and lower body fat ratio (p = 0.003), significantly higher CMJ height (p = 0.003), peak power (p = 0.015), mean propulsive force (p = 0.006), braking rate of force development (p = 0.026), and modified reactive strength index (p < 0.001) than NAIA guards. No statistically significant differences were found in IMTP performance between groups (p > 0.05). Basketball strength and conditioning coaches should consider focusing on improving force production at high movement velocities, while also maintaining a high muscle mass-to-body fat ratio in female collegiate guards.